Experimental and Theoretical Study on the Oxidation Mechanism of Dopamine in N-Octyl Pyridinium Based Ionic Liquids-Carbon Paste Modified Electrodes - Aguirre-Quintana, M; Aguirre-Quintana, M; Muena-Barria, J; Muena-Barria, J; Garcia-Sanhueza, C; Garcia-Sanhueza, C (2013)
This work describes the influence of n-octyl pyridinium cations based ionic liquids-carbon paste modified electrodes on the oxidation mechanism of dopamine. Ionic liquids formed by hexafluorophosphate anion and n-octyl pyridinium [R-OPy]+; R = CH3, H, CF3, where ionic liquids containing CH3 and CF3 are new products, were synthesized and characterized. Modified carbon paste electrodes with these salts were characterized by electrochemical impedance spectroscopy and cyclic voltammetry. Electrochemical oxidation of dopamine was studied in PBS buffer solution at pH = 7.4. The influence of the ionic liquids in the oxidation of dopamine was studied by cyclic voltammetry and rotating disk electrode. The results show that typical carbon paste electrode presents an electrochemical/chemical mechanism; whereas [OPy]PF6 and [CF 3-OPy]PF6 modified electrodes present an electrochemical/chemical/electrochemical mechanism. The experimental study is complemented with a theoretical analysis of substituent effects in terms of the molecular electrostatic potential, Mulliken population analysis and second order perturbation theory probed at the cation moiety of the IL. These indices consistently show an electron density accumulation at the ipso position of the pyridinium moiety of the IL that is in agreement with the electrochemical characterization. © 2013 Elsevier Ltd.